Awareness and Understanding of Enaira in Nigeria - Akindipe, Oluwaleke Ebenezer; Akhimie, Debbie; Olonade, Olanrewaju (Acta Universitatis Danubius. Œconomica, 2023)
A central bank digital currency (CBDC), also known as a digital currency produced by the central bank, has recently attracted the attention of numerous major banks. A central bank digital currency (CBDC) is a liability of the central bank issuing it and is the digital representation of real money. The aim of the study is to evaluate the awareness, understanding, and receptiveness of the E naira in Nigeria. The specific objectives are to examine the evolution and understanding of the eNaira and its impact on the Nigerian Emerging economy and to find out how the eNaira awareness will improve financial inclusion in Nigeria's emerging economy. A survey research design was adopted, and primary data was used for the study. The population of the study were 33 banks that joined the eNaira platform of the CBN, and ten banks that were actively involved in eNaira operations were used as the sample. One hundred twenty copies of the questionnaire were administered to respondents from the selected banks, and descriptive statistics were used to analyze the retrieved questionnaires. Regression analysis was used to test the hypothesis, and the result showed that the level of awareness, understanding, and receptiveness is low in Nigeria. It was concluded that the initiative has not yet progressed past the initial wave of early adopters regarding market receptivity, and the number of retail clients on board is less than 1% of active bank accounts. It was recommended that CBDC could be a catalyst in an economy like Nigeria, which is lagging behind in mobile money penetration. It would be crucial for banks to create their CBDC technology models to allow compatibility with other CBDC systems to enhance strong coordination and information sharing among central banks, which will be extremely helpful as they work together to maximize this new technical innovation.